Are Household Food Expenditures Responsive to Entry Into the Supplemental Nutrition Assistance Program?. (6th August 2015) - Kim, Jiyoon (June); Shaefer, H. Luke
Abstract : Objective: This study examines changes in household food expenditures in the months directly around entry into the Supplemental Nutrition Assistance Program (SNAP). Methods: Using monthly data on SNAP participation from the Panel Study of Income Dynamics (PSID), we estimate food‐expenditures‐to‐food‐needs ratio with an event‐study specification. Results: Upon entering the program, a substantially lower share of out‐of‐pocket spending accounts for SNAP households' food budgets. However, these expenditures are largely replaced with SNAP benefits, resulting in little changes in total food expenditures. We also identify the co‐occurrence of household economic shocks at the point of SNAP entry. Conclusion: SNAP entry is preceded by reduced rates of employment and marriage among heads of households, suggesting that household economic shocks may trigger SNAP entry. We find that SNAP benefits visibly appear to act as an important safety net for households who have recently entered the program, cushioning them from the extent of a negative shock in food expenditures that they might otherwise have faced.